Determinación del potencial de captura de carbono en cultivos de cacao, palma aceitera y una especie forestal (bolaina) en el área de influencia de la empresa palmas del Shanusi S.A; ubicada en la localidad de Pampa Hermosa – Yurimaguas - Ramírez García, Jason (2013)
The amount of carbon stored in species of oil palm (Eiaeis guinensis), with ages of 3 years and a half, which do not present formation of a Stipe defined to determine a DAP and specify the biomass of the plant. In this case was to combine two methods allometric (Bronw 1997 and Courley 1971 method) to determine the tree biomass. In case of having a DAP defined, with heights average > 1.5 m, is easy determine the biomass Arborea, having as antecedent that the biomass leaf is the 65 %(Biomasa Tronco). According to Bronw 1997. According to the obtained analysis method Bronw helped us to determine the biomass of the Stipe or stem assuming a perfect cylinder and the Courley method to determine the Foliar biomass, taking into account the sheet N ° 17 defined training and cross sections of the same. • According to results obtained carbon storage in ages 3-4 ai'ios is 61.86 Tn/searched/ai ' io (only includes biomass Arborea), result to the com...